The effects of contested divorce on adolescent’s and parent’s resilience - Tárnokiné Törő, Krisztina; Nora Pazdera; Luca Adamy; Anna Bártfai; Eva Hadházi PhD; Andrea Kövesdi; Szabolcs Takács; Rita Földi (IJRDO - Journal of Social Science and Humanities Research, 2019)
Purpose: The aim of this study is to investigate self and parent rated resilience in adolescence after contested divorce. Methods: Using resilience questionnaire contains 10 items and its purpose is to measure the ability of emotional resistance. Inclusion criterion were: children had to be 10- 18 years old and previously participate in the investigation of a forensic expert hence the critic divorce (contested divorce group). Controll group: children whose parents are still together. The experimental group contained 22 girls and 17 boys, the control group 21 girls and 17 boys. The sexes’ distribution between the two groups was not significantly different. Results : Those adolescents who went through contested divorce see their own resilience significantly weaker than those who live in a complete family (d(56,1)= -4,738, p=0,0000***). Mothers who had contested divorce also see their child’s resilience weaker than mothers who did not (d(61,4)=-3,217, p=0,0021**). The resilience of the mothers shows significant difference between the two groups. Our tests show significant difference between those fathers’ resilience who went through contested divorce and those who did not. Conclusions: For psychologists in clinical practice the importance of our results is that it is vital to strengthen adolescents’ self-confidence, sense of competence, if their parents went through a contested divorce, because these factors improve resilience.